Let [tex]A[/tex] be the event that a randomly selected person has the condition, and [tex]B[/tex] the event that the test returns a positive result. We are given that
[tex]P(A)=0.08[/tex]
[tex]P(B\mid A^C)=0.01[/tex] (false positive; that is, the event that the test incorrectly returns a positive result)
[tex]P(B^C\mid A)=0.01[/tex] (false negative; incorrectly returns a negative result)
We want to find [tex]P(A\mid B)[/tex]. By definition of conditional probability,
[tex]P(A\mid B)=\dfrac{P(A\cap B)}{P(B)}[/tex]
By the same definition,
[tex]P(A\cap B)=P(B\mid A)P(A)[/tex]
and by the law of total probability,
[tex]P(B)=P(A\cap B)+P(A^C\cap B)=P(B\mid A)P(A)+P(B\mid A^C)P(A^C)[/tex]
So we have (and this is known as Bayes' rule)
[tex]P(A\mid B)=\dfrac{P(B\mid A)P(A)}{P(B\mid A)P(A)+P(B\mid A^C)P(A^C)}[/tex]
[tex]\implies P(A\mid B)=\dfrac{0.99\times0.08}{0.99\times0.08+0.01\times0.92}\approx0.9[/tex]